DISKRIMINASI MUSLIM DALAM FILM BULAN TERBELAH DI LANGIT AMERIKA 2015 - Yusanto, Freddy; Gunawan, Herlandi Elvan (PRoListik : Jurnal Ilmu Komunikasi, 2022)
Film, as a mass communication media, has a main function as a means of delivering messages which related with science, culture, morals, social and religion to audiences. The message is visually presented, as well as delivers a meaningful message for the audience, such as discrimination cases. Discrimination might occur in the community with minority religions; in America for example, Muslims are considered as a minority religion. Discrimination against Muslims in America after the bomb attacks on WTC was then represented in the film of Bulan Terbelah di Langit Amerika (Moon splitted out in the sky of America). The method used in this research is contents analysis of semiotics by John Fiske. This study aims to determine how the discrimination experienced by Muslims in the film of Bulan Terbelah di Langit Amerika. To achieve the objectives of the study, researchers used qualitative descriptive method. The results of this study concluded that in the film of Bulan Terbelah di Langit Amerika occurs both direct and indirect discrimination shown through the gesture and dialogue between the characters in the film.